(untitled) (Research, Society and Development, 2022)
In the state of Minas Gerais, water abstraction below 1.0 L/s does not need to be authorized, but requires a registration of insignificant use. The hypothesis of this work is that these registrations for water abstraction issued in series along small stretches of a watercourse can substantially alter its water availability, and consequently cause environmental impacts, as well as lead to conflicts over water use. In this sense, the objective was to analyze the Water Resources State Policy of Minas Gerais, regarding the insignificant uses, contributing to the knowledge of the interference of these uses in the surface water availability of the hydrographic basin of the Suaçuí river - MG. For this, the list of surface water users in the study area was obtained from the Instituto Mineiro de Gestão das Águas. The water availability of the basin was calculated by stretches of watercourses, analyzing the interference of insignificant uses. Analyzing all the stretches in which insignificant uses are present, 555 were found to be unavailable, most of these stretches being of small extension, located in headwater regions of the study area, and also stretches where there are two or more catchments considered insignificant, or in consecutive stretches. This result suggests that the way that insignificant use registrations are granted should be revised, taking as a basis the water availability of the stretch to be demanded, and not only limited by a maximum flow.